Salvation by Faith in the Age of Consumerism : The Relevance of Sola Fide for Spirituality Evangelicalism Today - Banarto, Kris; Welly Kansil, Dicky (Devotion : Journal of Research and Community Service, 2025)
The phenomenon of consumerism in the modern era has influenced various aspects of human life, including Christian spirituality. Consumerism places the value of life on material possessions, luxury, and personal achievement, often shifting the understanding of faith to merely a means of obtaining physical blessings. This poses a challenge for the Evangelical movement rooted in the doctrine of sola fide, namely the belief that salvation is obtained only through faith in Jesus Christ, not through human effort or achievement. The main problem examined in this research is how the relevance of sola fide can be understood and lived out in a society dominated by a consumerist mindset. The purpose of this research is to explain the theological meaning of sola fide according to the Bible, analyze the influence of consumerism on Evangelical spirituality, and emphasize the practical relevance of the doctrine for the life of faith today. This research uses a qualitative method with a literature study approach and Evangelical hermeneutic analysis of the biblical text and the thoughts of Evangelical theologians. The results show that sola fide rejects spirituality that is centered on achievement or material wealth, affirming that the believer's identity is entirely rooted in God's grace in Christ. Consumerism has been proven to weaken the sense of faith by replacing God's grace with worldly values. Therefore, sola fide has contextual relevance for correcting and renewing evangelical spirituality, guiding the church to teach a simple lifestyle, pure faith, and a focus on Christ as the center of salvation.